AUTEKOLOGI AKASIA (Acacia nilotica) (L.) Willd. ex. Del DI TAMAN NASIONAL BALURAN JAWA TIMUR - Djufri Djufri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
This research aim to to know : ( 1).  Live cycle of A. nilotica, ( 2). Sspreading and Seed production in BNP, ( 3). Potency of A. nilotica as species bioprosfektif, and ( 4) Stand structure of A. nilotica in BNP.Research method used to know  cycle live,  spreading and seed production in BNP  and the done conducted stand structure with  direct perception  in field. Produce seed used  a square method  having a nest counted 10 fruit by using  plastic. obtained stand structure data with  madely is permanent square for the width of 20 m x 20  m of counted 15 fruit, and at each square measured by a diameter and high counted 10 tree. While data to know potency A. nilotica  as species biprospektif obtained from data  relevant secunder with problems  checked.Conclusion from this research is : (1). There are six  cycle step live A. nilotica that is seed corps, seedling, juvinile, adult, flower, and seed in pod, ( 2). Production of seed/tree at age 3 year gyrate  506seed/tree. : (3). Seed spreading A. nilotica in BNP through animal  like bull, wild buffalo, deer and others,  and also water at the rains season, ( 4). Potency of A. nilotica  as species bioprospektif can be developed  forestry, health, and also industrial,  and ( 5). Stand structure A. nilotica in BNP pertained  as strightened age.